2007
DOI: 10.1080/14622200601080281
|View full text |Cite
|
Sign up to set email alerts
|

Self-help cessation programs for smokeless tobacco users: Long-term follow-up of a randomized trial

Abstract: This paper presents long-term outcomes of the largest clinical trial of smokeless tobacco (SLT) cessation reported to date. SLT users in five northwestern states were recruited to call a toll-free number, and 1,069 users were randomized to one of two self-help conditions: either a manual-only condition or an assisted self-help condition, which included the manual, a targeted video, and two support phone calls. Significant between-group differences were not found for either the 12- or 18-month point-prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…However, we found no additive or synergistic benefit of offering both the Web and Quitline interventions, as has been observed for smoking cessation (Graham et al, 2011). Although our abstinence rates for Quitline counseling are substantially higher than those typically reported for smoking cessation (Stead et al, 2013), the overall abstinence rates achieved in this trial for all groups – including the Control – are consistent with the results obtained in earlier smokeless tobacco cessation studies that used low intensity interventions (Ebbert, Severson, Croghan, Danaher, & Schroeder, 2009; Severson, Akers, Andrews, Lichtenstein, & Jerome, 2000; Severson, Andrews, Lichtenstein, Danaher, & Akers, 2007; Severson et al, 2008). …”
Section: Discussionsupporting
confidence: 86%
“…However, we found no additive or synergistic benefit of offering both the Web and Quitline interventions, as has been observed for smoking cessation (Graham et al, 2011). Although our abstinence rates for Quitline counseling are substantially higher than those typically reported for smoking cessation (Stead et al, 2013), the overall abstinence rates achieved in this trial for all groups – including the Control – are consistent with the results obtained in earlier smokeless tobacco cessation studies that used low intensity interventions (Ebbert, Severson, Croghan, Danaher, & Schroeder, 2009; Severson, Akers, Andrews, Lichtenstein, & Jerome, 2000; Severson, Andrews, Lichtenstein, Danaher, & Akers, 2007; Severson et al, 2008). …”
Section: Discussionsupporting
confidence: 86%
“…It is possible that the content we provided in our Basic Condition may have exceeded the boundaries of this treatment-as-usual model. For example, the Basic Condition provided participants with an online version of the best-practices ST cessation Enough Snuff guide (Severson & Gordon, 2005) that has proven efficacious when delivered in printed format (Severson, Akers, Andrews, Lichtenstein, & Jerome, 2000;Severson et al, 2007;.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate items for this scale were drawn from the following sources: a version of the Fagerström scale used in previous studies (Severson, Andrews, Lichtenstein, Danaher, & Akers, 2007; Severson, et al, 2000); a 5-item version of the Cigarette Dependence Scale (CDS-5) (Etter, et al, 2003) we adapted for ST; items from subscales for stimulation, sedation, and morning use (Hudmon, et al, 2003) adapted for ST; and items representing behavioral and withdrawal facets of ST use created by the research team. The resulting 36-item scale was completed by 247 participants in an earlier ST cessation intervention who reported that they were still using ST (Severson, et al, 2000).…”
Section: Methodsmentioning
confidence: 99%